Non-null distribution of Kullback's statistic for testing equality of correlation matrices (2022)
In this article, we derive the asymptotic non-null distribution of Kullback’s statistic L∗ for testing equality of several correlation matrices. First, the distribution of a function of L∗ is obtained in series involving cumulative distribution function of a standard normal distribution by inverting the characteristic function from which the distribution of L∗ is deduced.